Research Progress on Anti‐Inflammatory Mechanisms of Black Ginseng. Issue 3 (10th March 2023) - Huo, Ran; Wang, Mengyuan; Wei, Xu; Qiu, Ye
Abstract: In recent years, black ginseng, a new type of processed ginseng product, has attracted the attention of scholars globally. Ginsenoside and ginseng polysaccharide, the main active substances of black ginseng, have been shown to carry curative effects for many diseases. This article focuses on the mechanism of their action in anti‐inflammatory response, which is mainly divided into three aspects: activation of immune cells to exert immune regulatory response; participation in inflammatory response‐related pathways and regulation of the expression level of inflammatory factors; effect on the metabolic activity of intestinal flora. This study identifies active anti‐inflammatory components and an action mechanism of black ginseng showing multi‐component, multi‐target, and multi‐channel characteristics, providing ideas and a basis for a follow‐up in‐depth study of its specific mechanism. Abstract :